Design and Characterization of Sodium Alginate and Poly(vinyl) Alcohol Hydrogels for Enhanced Skin Delivery of Quercetin - Ludovico Esposito; Ana Isabel Barbosa; Tânia Moniz; Sofia Costa Lima; Paulo Costa; Christian Celia; Salette Reis (MDPI AG, 2020)
Nature has led to the discovery of biopolymers with noteworthy pharmaceutical applications. Blended biopolymers have demonstrated promising characteristics when compared with their individual counterparts. Sodium alginate (SA) is a marine polymer that has demonstrated the ability to form hydrogels, an interesting property for the development of cutaneous formulations. Predicting the good performance of blended biopolymers, a novel series of hybrid hydrogels based on SA and poly(vinyl) alcohol (PVA) were prepared. Quercetin, a natural polyphenolic flavonoid commonly found in fruits and vegetables, is widely known for its strong anti-inflammatory and antioxidant activity, thus with potential applications against melanoma, dermatitis, psoriasis, and skin ageing. Here, hydrogels were produced at different ratios of SA and PVA. The surface morphology, structure, interaction of polymers, the capacity to absorb water and the entrapment efficiency of quercetin were evaluated for the blended hydrogels. Targeting the cutaneous application of the formulations, the rheological properties of all unloaded and quercetin-loaded hydrogels revealed pseudoplastic behavior, evidence of non-thixotropy, good resistance to deformation, and profile maintenance with temperatures ranging from 20 °C up to 40 °C. The incorporation of quercetin in the hydrogel retained its antioxidant activity, confirmed by radical scavenging assays (ABTS and DPPH). The permeability of quercetin through the skin showed different penetration/permeation profiles according to the hydrogel's blend. This behavior will allow the selection of SA-PVA at 2/1 ratio for a local and prolonged skin effect, making the use of these hydrogels a good solution to consider for the treatment of skin ageing and inflammation.